The Tax Write-Off as a New Form of Financing Religious Communities in Poland - Mielczarek , Mikołaj (Studia Oeconomica Posnaniensia, 2016)
The article attempts to assess the fi scal impact of the Government’s pro- posals for the revision of the method for fi nancing religious communities in Poland. Currently a substantial number of these communities are financed from the Church Fund, which is completely fi nanced by a grant from the state budget. Th e project involves the replacement of the Church Fund by a write-off amounting to 0.5% of the applicable personal income tax. A similar solution exists in Spain, the Netherlands, Hungary and Italy. In Poland nearly 89% of the inhabitants claim affi liation to a church or religious organization. Th e simulation relating to the years 2000-2015 showed that income from tax deductions was a more effi cient source for those communities than funding received from the Church Fund. Simultaneously the liquidation of the fund means a reduction of budget expenses.